Socio-Cultural, Organizational, and Community Level Influences on Physical Activity Levels of Latino Preschool-Age Children: A Qualitative Study - Lindsay, Ana C.; Greaney, Mary L.; Sussner, Katarina M.; Pfeiffer, M. Erin; Peterson, Karen E. (International Journal of Child Health and Nutrition, 2014)
Objectives: As more children grow up in families with immigrant parents of Latino origin, there is a need to understand key influences on physical activity behaviors of young Latino children to prevent obesity in this high-risk group. Design: We conducted six focus groups with low-income Latina mothers (N = 33) whose preschool-aged children (2-5 years) were enrolled in the Supplemental Nutrition Program for Women, Infants and Children (WIC) program in Rhode Island. Data was analyzed using content analysis to identify recurrent themes. Results: Despite understanding the importance of physical activity for overall health, physical activity was not a top priority for the Latino mothers participating in the focus groups. Mothers reported facing numerous barriers to establishing and maintaining healthful physical activity habits for their preschool-aged children and themselves, particularly financial and socio-cultural barriers. Analyses revealed that Latina mothers perceive the WIC as a program focused on the development and maintenance of healthy eating habits and nutritional status of children and not physical activity. Conclusions: Recognizing the importance of socioeconomic position and the influence of cultural factors on physical activity is essential if effective prevention and intervention programs for Latino families and their children are to be designed. Study findings emphasize the importance of the family as a central unit of change and suggest that successful interventions to promote physical activity of low-income Latino preschool children must take into account the needs and constraints of the family unit as a whole. The WIC program has the potential to be a venue for promoting awareness of and educating low-income Latino parents about the importance of helping their children develop and maintain early healthful physical activity habits. The WIC program can also play an important role in facilitating access and creating programs and services that provide increased opportunities for physical activity of young children and their families.